Exploring the Relationship of Image Formation on Tourist Satisfaction and Loyalty: Evidence From China - Jebbouri, Abdelhamid; Zhang, Heqing; Wang, Lei; Bouchiba, Nasser (Frontiers in Psychology, 2021)
Cultural heritage tourist destinations have emerged as a hot topic in the tourism literature, but there have been relatively few studies to determine the role of local participation involvement in either tourism planning or tourists’ decision-making processes. The connection between local community participation, authenticity, access to local products, destination visit image, tourist satisfaction, and tourist loyalty is thus relatively unexplored in the literature. This study used a quantitative approach based on a survey with 406 respondents visiting the city of Kaiping in Guangdong, China. The proposed hypotheses were empirically tested with SPSS and AMOS. The resulting outcomes indicate a positive correlation between local community participation, authenticity, and access to local and destination visit image, which led to tourist satisfaction and ultimately resulted in tourist loyalty. Additional theoretical contributions, practical implications, and limitations are also discussed.